2021
DOI: 10.3390/molecules26196077
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies on Therapeutic Effects of Cannabidiol in Neural Cells: Neurons, Glia, and Neural Stem Cells

Abstract: (‒)-Cannabidiol (CBD) is one of the major phytocannabinoids extracted from the Cannabis genus. Its non-psychoactiveness and therapeutic potential, partly along with some anecdotal—if not scientific or clinical—evidence on the prevention and treatment of neurological diseases, have led researchers to investigate the biochemical actions of CBD on neural cells. This review summarizes the previously reported mechanistic studies of the CBD actions on primary neural cells at the in vitro cell-culture level. The neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 132 publications
(191 reference statements)
1
22
0
Order By: Relevance
“…Primary microglia and neurons were extracted from the brains of neonatal female C57/BL6J mice (n = 32; 1-2 days old) as previously described [27]. The microglia were cultured in Neurobasal-A medium containing 2% B27, 2-mM L-glutamine, 50-U/ml penicillin, and 50-U/ml streptomycin (Gibco, USA).…”
Section: Cell Lines and Treatmentsmentioning
confidence: 99%
“…Primary microglia and neurons were extracted from the brains of neonatal female C57/BL6J mice (n = 32; 1-2 days old) as previously described [27]. The microglia were cultured in Neurobasal-A medium containing 2% B27, 2-mM L-glutamine, 50-U/ml penicillin, and 50-U/ml streptomycin (Gibco, USA).…”
Section: Cell Lines and Treatmentsmentioning
confidence: 99%
“…Recently, the neuroprotective capability of CBD against OS, as well as its toxicity profile on in vitro culture, is systematically pursued. Although CBD showed both neurotoxic and neuroprotective effects on hippocampal neurons, the use of low-concentrated (i.e., 5 μM) CBD did not cause toxic effects and significantly rescued the neurons from OS, confirming its neuroprotection capability [ 26 ].…”
Section: Cbd and Neurodegenerative Diseasesmentioning
confidence: 99%
“…(-)-Cannabidiol (2-[(1R,6R)-3-methly-6-prop-1-en-2-ylcyclohex-2-en-1-yl]-5-pentylbenzene-1,3-diol, CBD), one of the major cannabinoids in the Cannabis genus, has ethnopharmacologically been suggested to have various health benefits, including anti-cancer, anti-epileptic, anxiolytic, anti-inflammatory, and neuroprotective effects. [1][2][3][4][5][6] Unlike tetrahydrocannabinol (THC) that is another main cannabinoid extracted from Cannabis, CBD is not psychoactive. According to the WHO Expert Committee on Drug Dependence, CBD has low toxicity and good safety profiles (e.g., no alterations of heart rate, blood pressure, and body temperature), but some clinical studies have reported mild DOI: 10.1002/adbi.202300090 adverse effects of CBD in the nervous system (e.g., headache, dizziness, and somnolence) and in the gastrointestinal system (e.g., diarrhea and nausea).…”
Section: Introductionmentioning
confidence: 99%
“…The neurotoxicity studies on CBD would be particularly informative and beneficial in the healthcare sector, considering much interest in CBD against neurological diseases, [6] as well as recent U.S. Food and Drug Administration (FDA) approval of CBD as a treatment of seizures associated with Lennox-Gastaut syndrome, Dravet syndrome, or tuberous sclerosis complex in patients 1 year of age or older. [7][8][9] However, fundamental studies on the cytotoxicity of CBD in neurons, a major cell type that executes main functional roles in the nervous system, still have been limited.…”
Section: Introductionmentioning
confidence: 99%